Vascular Trauma Experience at Lady Reading Hospital Peshawar - Khan, Jalal; Aslam, Sohail; Anwar, Riaz; Ahmad, Taskeen; Rehman, Khalid; Waseem, Nayyar; Majeed, Abdul; Ahmad, Hamid; Mannan, Parvez (Journal of Postgraduate Medical Institute, 2011)
To evaluate vascular trauma management mainly on clinical assessment, at a less equipped setup and compare the outcome in early and late arrivals. A prospective study of vascular trauma patients was conducted at Lady Reading Hospital Peshawar. The nature, site, early and late presentation and outcome of surgery in vascular injuries presenting to our department between January 1995 to December 1998 were assessed. Out of these cases, only few stable neck injuries had pre-opearative agniographies. There were 354 vascular injuries in 344 patients (mean age 29, range 5 - 60). mechanism and nature of injuries were assessed. Early presentations (group A: 112 cases < 8 hours) were compared with complications, associated injuries and outcome were accorded.